Do the competition rules of synchronized swimming encourage undesirable levels of hypoxia? - Davies, B. N.; Donaldson, G. C.; Joels, N. (British Journal of Sports Medicine, 1995)
Recent anecdotal reports that some synchronized swimmers have become dizzy or disorientated towards the end of their performance, and in the worst cases fainted underwater, have caused concern. However, the rules of synchronized swimming encourage slow performance of compulsory figures, and an analysis of the competition placings and duration of underwater sequences showed that the highest rankings were gained by slowly performed compulsory figures and free programmes containing a long underwater sequence. The combination of breath-holding and the vigorous exercise involved suggests that some of the symptoms complained of by the swimmers might be due to hypoxia. We therefore studied the alveolar gas tensions in nine members of the Great Britain National Squad immediately following the performance of set figures and the initial underwater sequence of their free routine in a swimming-bath. All were cyanosed after the underwater sequences of the free routine and reported being mildly confused. The mean(s.d.) alveolar PO2 at this stage was 5.07(1.1) KPa, while three girls had an alveolar PO2 below 4 KPa, the lowest being 3.67 KPa. These gas tensions suggest that potentially dangerous levels of hypoxia may develop during competitive synchronized swimming and that prolonged underwent sequences should not be encouraged.